Pentingnya Sepak Bola untuk Mengurangi Kecanduan Game Online di Era Digital - Waluyo, Gatot; Suhaemi, Suhaemi; Umar, Umar (Lembaga Publikasi Ilmiah Nusantara, 2025)
The rapid development of information and communication technology in today's digital era has significantly impacted the younger generation, one of which is online gaming addiction. This addiction can diminish the physical, social, and mental quality of young people, as well as disrupt their daily activities. In addressing this issue, soccer emerges as an effective alternative solution to reduce online gaming addiction. This study aims to explore the importance of soccer as a means to enhance physical activity, build social skills, and provide positive stimulation for the emotional development of young people. Through an approach involving observations and interviews with coaches, young players, and parents, this research finds that soccer can provide a healthy environment, improve social interaction, and foster a spirit of sportsmanship that helps divert teenagers' attention away from online gaming addiction. The results of this study are expected to provide a deeper understanding of the benefits of sports, particularly soccer, in shaping character and improving the well-being of the younger generation amid the dominance of digital technology.